2010
DOI: 10.1001/archoto.2009.231
|View full text |Cite
|
Sign up to set email alerts
|

Number of Descriptors in Cued Odor Identification Tests

Abstract: Cued odor identification tests with various numbers of verbal descriptors produce similar results. However, an increasing number of alternative descriptive items seem to allow for better discrimination between individuals with and without olfactory loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…However, the UPSIT can distinguish between actual anosmic patients and malingerers,13, 14 whereas the PST has a 99% sensitivity and 40% specificity for detecting anosmia 15. Other advantages to olfactory identification testing include effectiveness in discriminating among varying levels of olfactory function, low cost, and ease of administration compared to other instruments such as olfactory threshold testing 12, 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…However, the UPSIT can distinguish between actual anosmic patients and malingerers,13, 14 whereas the PST has a 99% sensitivity and 40% specificity for detecting anosmia 15. Other advantages to olfactory identification testing include effectiveness in discriminating among varying levels of olfactory function, low cost, and ease of administration compared to other instruments such as olfactory threshold testing 12, 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…We asked volunteers if they detected an odor and, if so, to describe it. Because there is increased accuracy in identification performance when provided verbal information (Hummel, Kobal, Gudziol, & Mackay-Sim, 2007;Negoias, Troeger, Rombaux, Halewyck, & Hummel, 2010), we felt the forced-choice test might fail to capture a true difference in identification ability. Further, forced-choice methods engage volunteers in the process of elimination, which may overcome individual variation in odor experience but may, more importantly, mask true olfactory ability by introducing guesswork (Kern, Wroblewski, Schumm, Pinto, & McClintock, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Global identification IG Real identification IR T = 0 (n = 5) 5.4 [2][3][4][5][6][7][8][9] 3.4 [0-9] T < 10th percentile (n = 7) 9 [4][5][6][7][8][9][10][11][12][13] 8.14 [3-3] T > 10th percentile (n = 1) 8 8 Passage of the 3 subtests of the Sniffin' Stick is time-consuming [11], which is why, in clinical practice, we use the TI version (threshold and identification tests) to evaluate the sense of smell in patients with nasal polyposis [5], as the combination of the two subtests was a more reliable tool to evaluate smell than use of only one of these subtests alone [1].…”
Section: Postoperative Tmentioning
confidence: 99%
“…Negoias et al showed that the number of choices of odours in the identification test played an important role in the diagnosis of olfactory dysfunction and contributed to more precise discrimination of various degrees of hyposmia [12]. The identification test comprises a mandatory choice, requiring the patients to respond randomly when they do not perceive any odour, as if they were not passing the test.…”
Section: Postoperative Tmentioning
confidence: 99%